Proposed Conception of Application of Standards Accounting Education and its Role in Quality Control of Accounting Curricula in Saudi Universities - Fatih Amin Abdelrahim (University of Science and Technology, Yemen, 2014)
Proposed Conception of Application of Standards Accounting Education and its Role in Quality Control of Accounting Curricula in Saudi Universities le for TQM Indicators: Dhi Qar university as a Model            Abstract Proposed Conception of Application of Standards Accounting Education and its Role in Quality Control of Accounting Curricula in Saudi Universities This research is based on a proposed conception of application of standards accounting education and its role in quality control of accounting curricula in Saudi universities. The rationale behind the study was the in adherence to international standards when designing accounting courses at universities, which fact that negatively affects the quality of accounting and is reflected in neglect of training aspects during study. Hence, this research aims to shed light on international education accounting and how it can be utilized when designing accounting courses within universities. The secondary goals include study and analysis of standards of accounting education and how they can be made use of in designing accounting courses(syllabuses), as well as drawing a framework that can guide in designing and evaluating these courses. The researcher has reached a number of conclusions, namely that standards of accounting education provide explicit directions for designing accounting courses, as they provide measurable and verifiable learning outcomes. In addition, the modified standards of accounting education provide clear- cut guidelines that can aid in determining the learning outcomes expected of accounting courses. Also, a positive correlation was established between the standards of accounting education and the standards of National Commission for Academic Accreditation and Assessment in Saudi Arabia(NCAAA). Moreover, the researcher has concluded that continuous professional  development is necessitated by pressing issues such as globalization , expansion of enterprises and technological development. The researcher has put forward a number of recommendations such as the need to adopt the standards for accounting education issued by the international federation of accountants(IFAC),and those by Commission of academic assessment and accreditation as measurements when undertaking an assessment or accreditation for accounting courses. The adoption of this standards also renders attainment of international recognition of methods of accounting education in a particular country easier. Finally, courses should be designed in such away as to allow for speedy responses to changing circumstances.